EFEK PSIKOLOGIS PEMBACAAN DZIKIR TERHADAP KESEHATAN MENTAL DI ERA DIGITAL - Budi Mulya (Yayasan An-Nur Meunara Baro, 2025)
This study investigates the psychological effects of dzikir (Islamic remembrance) on the mental health of young Muslims in the digital era. The research stems from the increasing phenomenon of digital fatigue and spiritual crises caused by overexposure to online content. Dzikir is examined not only as a religious ritual but also as a cost-effective digital detox strategy rooted in neuroscience. Using a mixed-methods approach, the study involved 100 Muslim participants aged 18–35 who are active on social media. Data were collected through the DASS-21 survey, 30-day reflective journals, in-depth interviews, and content analysis of online trends. Results show that 78% of participants reported reduced screen-induced anxiety and 65% experienced improved sleep quality through regular dzikir. Neuropsychological findings using fMRI indicate increased prefrontal cortex activity during dzikir recitation. The discussion critically explores the rise of